External validation of INCREMENT-CPE score in a retrospective cohort of carbapenemase-producing Klebsiella pneumoniae bloodstream infections in critically ill patients. (June 2021) - Papadimitriou-Olivgeris, Matthaios; Bartzavali, Christina; Georgakopoulou, Alexandra; Kolonitsiou, Fevronia; Mplani, Virginia; Spiliopoulou, Iris; Christofidou, Myrto; Fligou, Fotini; Marangos, Markos
Abstract: Objectives: Our aim was to validate the INCREMENT-CPE score (ICS) in patients hospitalized in the intensive care unit (ICU) with bacteraemia due to carbapenemase-producing Klebsiella pneumoniae (CP-Kp). Methods: The study was conducted in the ICU of the University General Hospital of Patras, Greece, during a 10-year period (2010–2019). Patients with monomicrobial bacteraemia due to CP-Kp were included. Primary outcome was 14-day mortality. MICs of meropenem, tigecycline, fosfomycin and ceftazidime/avibactam were determined by Etest, whereas for colistin the broth microdilution method was applied. PCR for bla KPC, bla VIM, bla NDM and bla OXA genes was used. Results: Among 384 CP-Kp bacteraemias, most were primary (166, 43.2%) followed by catheter-related (143, 37.2%). Most isolates carried bla KPC (318, 82.8%). Fourteen-day mortality was 26.3% (101 patients). ICS score was 11.1 ± 4.2. An ICS ≥10 showed a sensitivity of 98.0% and a negative predictive value of 98.7%. The area under the curve of ICS (0.800) was comparable to those of the Pitt bacteraemia score (0.799), the Simplified Acute Physiology Score II (SAPS II) (0.797) and the Sequential Organ Failure Assessment score (SOFA) (0.815). Conclusions: ICS showed predictive efficacy similar to that of the SAPS II, SOFA and Pitt bacteraemia scores.